Pathology of acute myocardial infarction with particular reference to occlusive coronary thrombi. Issue 7 (July 1976) - Davies,, M J; Woolf, N; Robertson, W B
Abstract : Analysis of the pathological findings in 500 cases of fatal acute myocardial infarction showed that in 469 this was localized to one transmural area of the left ventricle; in 31 there was diffuse subendocardial necrosis. In the former occlusive coronary thrombus was found in the related artery in 95 per cent of cases. Variation in the percentage of occlusions found was noted between different prosectors and when coronary artery calcification was present. Only 4 of the 31 patients with subendocardial necrosis had recent occlusion; triple vessel disease was common in this group suggesting general failure of coronary perfusion. It is essential in necropsy studies of the relation of coronary thrombosis to myocardial infarction to be sure that muscle necrosis is present, to distinguish the two forms of myocardial necrosis, and to employ a meticulous dissection technique with decalcification of the arteries when necessary.